PERLINDUNGAN HUKUM TERHADAP KONSUMEN DALAM TRANSAKSI E-COMMERCE MELALUI MEDIA SOSIAL INSTAGRAM - Septian, Fazrian; Rahmatiar, Yuniar; Abas, Muhamad (Collegium Studiosum Journal, 2023)
The development of technology in this case is something related to human life, where technology on the other hand provides convenience but also provides new problems that are accepted by humans. The internet is one form of technological development itself. The internet is an electronic media and information that is developing very fast. The internet is widely used in various trading activities, trading activities that utilize the internet are known as e-commerce, one of the internet trading activities is through the Instagram platform. Trading via Instagram social media itself raises many problems related to law with all the risks. Problems that can arise include default. The purpose of this article is to find out the rights and obligations of the parties in buying and selling transactions via Instagram and the legal consequences that arise if the seller in a buying and selling transaction via Instagram defaults. In this study the authors used empirical research methods. The data taken was in the form of secondary and primary data. Secondary data was obtained from interviews with informants who had cases related to purchases on Instagram social media. Primary data were obtained from Civil Law, literature studies and various articles related to the problems studied. The results obtained from this writing are that legal protection for consumers who feel harmed by irresponsible producers has been regulated in Law no. 8 of 1999. The research in this article concludes that: in buying and selling activities carried out on Instagram there are often deviations in rights and obligations that are no longer in accordance with the norms that exist in society and legal remedies that can be taken in the event of default from one of the parties, both sellers and buyers who make online transactions, can be sued in the general court environment or outside the court and can be fined directly for the party who commits the default.